Diné dóó Gáamalii: Navajo Latter-Day Saint experiences in the twentieth century - King, Farina (Lyda Conley series on trailblazing indigenous futures, 2023)
"Dine doo Gaamalii is a history of twentieth-century Navajos, including author Farina King and her family, who have converted and joined the Church of Jesus Christ of Latter-day Saints (LDS), becoming "Dine doo Gaamalii"--both Dine and LDS. Drawing on Dine stories from the LDS Native American Oral History Project, King illuminates the mutual entanglement of Indigenous identity and religious affiliation, showing how their Dine identity made them outsiders to the LDS church and, conversely, how belonging to the LDS community made them outsiders to their Native community. The story that King tells shows the complex ways that Dine people engaged with church institutions within the context of settler colonial power structures. The lived experiences of Dine in the church programs sometimes diverged from the intentions and expectations of those who designed them"--